Responses of Liolaemus lizards to environmental heterogeneity: Linking microhabitat selection and thermal ecology in southern Patagonia - Candela Victorel; Mauro I. Bonavita; Martin C. Castillo; Débora L. Moreno Azocar; María G. Perotti; Félix B. Cruz; Oscar A. Stellatelli (Journal of Thermal Biology, 2026)

Medicinal plants for anxiety: Global evidence on species verified in the Philippine flora - Oliver Villaflores; Ross Vasquez; Yutaka Kuroki; Aya Wada; Xinyi Zhu; Denver Erick Almeria; Kyle Andrei Cabatit; Jonah Joshua Garcia; Janelan Martin; Agnes Llamasares-Castillo (Next Research, 2026)

Temperature and photoperiod interactions influence the cessation of wood growth in three temperate and boreal conifers - Jianhong Lin; Cyrille B.K. Rathgeber; Patrick Fonti; Sergio Rossi; Henri Cuny; Edurne Martinez del Castillo; Katarina Čufar; J. Julio Camarero; Alessio Giovannelli; Harri Mäkinen; Peter Prislan; Walter Oberhuber; et al. (Agricultural and Forest Meteorology, 2026)

Infrared Emission in the Second Biological Window in LaInO3:Ho3+ Exciting in the First Biological Window - Mauricio A. Vega-Pallauta; Rodrigo Castillo; Kevin Soler-Carracedo; Inocencio R. Martin (Journal of Fluorescence, 2025)

Site formation and post-sedimentary processes affecting Pleistocene archaeological record: depositional environments and sediment deformation at the Middle Palaeolithic site of Peña Cabra rock shelter (central Spain) - Luis Luque; Martin Kehl; José-Javier Alcolea-González; María de Andrés-Herrero; Samuel Castillo-Jiménez; Felipe Cuartero; Nicole Klasen; Ignacio Triguero; Antonio Alcaina; Gerd-Christian Weniger; Manuel Alcaraz-Castaño (Quaternary International, 2025)

Design, development and qualification of a european international berthing and docking mechanism (IBDM) - Joaquín Meléndez; Jeanette Bast; Johan Bogaerts; Jeremy Bouten; Angelo Costantino; Luc De Busser; Rutger De Nutte; Isabelle De Preter; Andy De Wilde; Felix De Wispelaere; Filip Dewitte; Wim Derkinderen; et al. (Journal of Space Safety Engineering, 2025)

Effect of air temperature, milk production and shearing on drinking water intake of Angora goats in pen during summer - Martin Calianno; Daniel A. Castillo; Santiago I. Hurtado; Saúl Deluchi; Brenda Garcia; Laura Villar; E. Sebastian Villagra; Marcos H. Easdale (Small Ruminant Research, 2025)

Effect of a feed additive based on a mix of condense and hydrolysable tannins (ByPro®) on lactating dairy cows milk production performance - Alejandro R. Castillo; Martin Pol; Mónica Gaggiotti; Julio A. Di Rienzo; Damiano Cavallini (Tropical Animal Health and Production, 2025)
The objective of this research was to evaluate the effect of a commercial mix of condensed and hydrolysable tannins feed additive to lactating dairy cows. Two high-scale dairy farm units, similar management and diets were used. All lactating cows in one unit were fed with the mix of tannins (ByPro ® 0.3%DMI), the other unit was the Control. Cows were categorized per DIM, 0 to 30, 31 to 120, 121 to 365, and more. Milk yield and composition was evaluated in all the lactating cows in each dairy unit at time 0, (initial), and after 4 weeks of supplementation (final). A linear model was adjusted for each variable. Estimated DMI and diets were similar in both dairy units, averaging 25.5 kg DMI/cow, as well as feed ingredients, dietary nutrient contents, and milk yield (34 kg milk/cow per day). Milk yield, from 0 to 365 DIM was increased ( P < 0.01) on supplemented cows (+ 2.3 ± 0.33 L milk/cow.d), with no effect on milk fat and protein contents. High data variability was observed on cows with 0–30 DIM, milk fat and protein content were reduced by ByPro without effect on milk yield. Positive responses of ByPro ® on milk, milk fat and protein contents from 31 to 120 and 121–365 DIM were observed, + 3.6 and + 3.2 kg milk/cow.d; +0.27% fat and + 0.21% protein; and + 0.17% fat, + 0.11% protein; respectively. The mix of tannins increased milk lactation performance on cows with more than 30 DIM.

Spatiotemporal Variability of Dendroecological Indicators in Pedunculate Oak ( Quercus robur L.) Tree‐Rings Across Europe in Relation to Species Distribution Models - Andrei Popa; Jernej Jevšenak; Marcin Dyderski; Radosław Puchałka; Allan Buras; Ionel Popa; Martin Wilmking; Aleksandra Kalisty; Catalin‐Constantin Roibu; Marcin Jakubowski; Eric Thurm; Martin Šenfeldr; et al. (Global Change Biology, 2025)
Climate is a primary, but non‐stationary, driver of tree growth. Climate change is altering the sensitivity of forest growth to water availability and temperature over time. It is considered that pedunculate oak ( Quercus robur L.) will cope with the changing climatic conditions in Europe in the near future. However, while species distribution models project expansion zones, they also identify reductions in occurrence at the dry and warm distribution margins. Whereas species distribution models primarily rely on occurrence data, tree rings—given their long‐term perspective and their use in empirical models—can provide a mechanistic view of forest growth dynamics, including temporally changing climate responses. Increased climate sensitivity and growth synchrony are key dendroecological indicators of tree stress. Here, we used an unprecedented network of 150 Q. robur sites (over 3300 trees), covering the full projected range of contracting to persistent areas across Europe, to assess the dendroecological indicators over recent decades in relation to species distribution model predictions. We reveal that oaks in areas projected to experience range contraction exhibited greater sensitivity to current growing season climatic conditions, whereas those in persistence areas responded more strongly to previous season conditions. Growth synchrony among trees was higher in the contraction areas, but showed no significant increasing trend over the last 70 years, as expected from ecotone theory. Temporal shifts in climate sensitivity were stronger for temperature and vapor pressure deficit in the persistence areas, whereas the climatic water balance gained importance in the contraction zones. These findings suggest that Q. robur growth is not yet being severely affected by climate change, and that the species is currently coping well with the climate changes, even in regions with projected range contractions, thereby challenging statistically derived scenarios of range shift based on species distribution models.

Interval resonance analysis (InRA): A versatile tool for automated untargeted 1H NMR fingerprinting – A case study in sugar beet field authentication - Cristian A. Fuentes; David Montoya; Mecit Öztop; Macarena Rojas-Rioseco; Martin Bravo; Francisca González; Rosario del P. Castillo (Analytica Chimica Acta, 2025)

A single-tree approach to determine climate-growth patterns of European beech and their seasonality in the species southern distribution area - Roberto Serrano-Notivoli; Jernej Jevšenak; Edurne Martinez del Castillo; Katarina Čufar; Nina Škrk-Dolar; Giovanna Battipaglia; Jesus Julio Camarero; Andrew Hacket Pain; Alistair Jump; Renzo Motta; Paola Nola; Momchil Panayotov; et al. (Agricultural and Forest Meteorology, 2025)

One well-planned and executed exchange is better than two: Lessons learned from a reciprocal fisheries learning exchange between Madagascar and Mexico - Katie R. Thompson; Steve Rocliffe; Alejandro Castillo López; Tinah Martin; S. Hoyt Peckham; Christian Portillo; Xavier Vincke; Lekelia D. Jenkins (Marine Policy, 2025)

Six decades of global coral bleaching monitoring: a review of methods and call for enhanced standardization and coordination - Andrea Rivera-Sosa; Aarón Israel Muñiz-Castillo; Ben Charo; Gregory P. Asner; Chris M. Roelfsema; Simon D. Donner; Brianna D. Bambic; Ana Gabriela Bonelli; Morgan Pomeroy; Derek Manzello; Paulina Martin; Helen E. Fox (Frontiers in Marine Science, 2025)
Coral bleaching poses a severe threat to the health and survival of global coral reef ecosystems, with recent events surpassing historical heat stress records. To address this crisis, improved long-term monitoring, communication, and coordination are urgently required to enhance conservation, management, and policy responses. This study reviews global coral bleaching survey methodologies and datasets spanning 1963 to 2022, identifying key challenges in methodological standardization, including database duplication and inconsistencies in naming and reporting bleaching metrics. These issues hinder comparative analyses and contribute to discrepancies in global bleaching impact assessments. We developed a typology of twenty-nine coral bleaching methods used across various scales, encompassing remote sensing tools, underwater surveys, and specimen collection. Analysis of 77,370 observations from three major datasets revealed that 9.36% of entries lacked methodological descriptions. Among recorded methods, belt transects (42%), line and point intercept transects (33%), and random surveys (17%) were the most widely applied. Practitioner surveys underscored the dominance of in situ transect and visual methods, highlighting the growing adoption of photo quadrats—an emerging yet underrepresented technique in existing datasets. To enhance global coral bleaching assessments, we propose a standardized framework that ensures open access and accessible data that aligns with decision-makers’ needs for efficient data aggregation and interoperability to better understand temporal and spatial bleaching events. A globally coordinated coalition should unify protocols, improve data-sharing capabilities, and empower regional networks through targeted training, incentives, and open communication channels. Strengthening field capacity in coral taxonomy and standardized survey methodologies, alongside integrating advanced tools, will improve data quality and comparability. Additionally, creating precise geolocated datasets will bridge on-the-ground observations with advanced remote sensing systems, refining the accuracy of satellite-based early warning tools. Establishing interoperable online platforms will further streamline data integration and accessibility, providing a robust foundation to support global responses to coral bleaching and foster impactful conservation initiatives.

Are all renewable energy sources the same? A comparative analysis of public perceptions and preferences for renewable energy types in Southeast Asian cities - Daniel del Barrio Alvarez; Nan Wang; Masahiro Sugiyama; Masako Numata; Truong Dang Thuy; Azlina Abd Aziz; Rosalina Palanca-Tan; Aung Ze Ya; Ariel Anshory Yusuf; Awang Noor Abd. Ghani; Gem Castillo; Martin Daniel Siyaranamual; et al. (Sustainability Science, 2025)
The realization of a sustainable energy transition in Southeast Asia will require the overcoming of the current high reliance on fossil fuels in the energy mix and the steady and rapid growth in energy demand in the region. To achieve an economically, socially, and environmentally sustainable energy transition in the region, it is vital to utilize all available renewable energy sources to the greatest extent possible. It is therefore essential to gain an understanding of how citizens in each country perceive the available renewables. However, the majority of existing literature in this region has been constrained by a narrow focus on a comparison between fossil and renewable energy. Furthermore, while previous research has predominantly concentrated on single-country analyses, there are significant implications that could be disseminated across ASEAN countries. In light of the aforementioned limitations of existing literature, this paper aims to make a contribution by undertaking a comparative analysis of public preferences for renewable energy sources in eight major urban areas in seven Southeast Asian countries. The findings of this study indicate that, while climate change (or global warming) is perceived as a significant issue, it is often regarded as a secondary concern compared to other environmental issues. This is despite the fact that many of these issues are closely interlinked with and would be exacerbated by climate change. Furthermore, the findings suggest that solar energy is the most preferred renewable source across all urban areas surveyed. In contrast, bioenergy (or biomass) is generally the least preferred source of energy in all cities. There is considerable variation in perceptions of wind, hydro, and geothermal energy, with a high degree of variability between and within countries. These similarities and differences in preferences for renewable energy sources appear to be associated with varying levels of knowledge or familiarity with each source, which is consistent with differing willingness to pay for each source. These findings highlight the necessity for policies that address this apparent lack of understanding of how the transition to a sustainable energy system and each renewable energy technology can help mitigate the impact of environmental problems highlighted in each society.

Multiscale analysis of the M1 MoVNbTeO catalyst for ethylene production via selective ethane oxidation: From atomistic calculations to the industrial reactor - José G. Rivera; Martin A. Purino; José F. Durán; Carlos Alvarado; Alberto Hernandez; Maarten K. Sabbe; Carlos O. Castillo-Araiza (Chemical Engineering Journal, 2025)

Interactive impact of residual pyrethroid compounds used in the Chilean salmon farming industry and coastal acidification conditions on the feeding performance of farmed mussels in northern Patagonia - Adonis Conejeros; Valeska A. San Martin; Nicole Castillo; L. Antonio Cuevas; Karen Garcés; Ricardo O. Barra; Victor M. Aguilera; Cristian A. Vargas (Marine Environmental Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

No Future Growth Enhancement Expected at the Northern Edge for European Beech due to Continued Water Limitation - Stefan Klesse; Richard L. Peters; Raquel Alfaro‐Sánchez; Vincent Badeau; Claudia Baittinger; Giovanna Battipaglia; Didier Bert; Franco Biondi; Michal Bosela; Marius Budeanu; Vojtěch Čada; J. Julio Camarero; et al. (Global Change Biology, 2024)
With ongoing global warming, increasing water deficits promote physiological stress on forest ecosystems with negative impacts on tree growth, vitality, and survival. How individual tree species will react to increased drought stress is therefore a key research question to address for carbon accounting and the development of climate change mitigation strategies. Recent tree‐ring studies have shown that trees at higher latitudes will benefit from warmer temperatures, yet this is likely highly species‐dependent and less well‐known for more temperate tree species. Using a unique pan‐European tree‐ring network of 26,430 European beech ( Fagus sylvatica L. ) trees from 2118 sites, we applied a linear mixed‐effects modeling framework to (i) explain variation in climate‐dependent growth and (ii) project growth for the near future (2021–2050) across the entire distribution of beech. We modeled the spatial pattern of radial growth responses to annually varying climate as a function of mean climate conditions (mean annual temperature, mean annual climatic water balance, and continentality). Over the calibration period (1952–2011), the model yielded high regional explanatory power ( R 2 = 0.38–0.72). Considering a moderate climate change scenario (CMIP6 SSP2‐4.5), beech growth is projected to decrease in the future across most of its distribution range. In particular, projected growth decreases by 12%–18% (interquartile range) in northwestern Central Europe and by 11%–21% in the Mediterranean region. In contrast, climate‐driven growth increases are limited to around 13% of the current occurrence, where the historical mean annual temperature was below ~6°C. More specifically, the model predicts a 3%–24% growth increase in the high‐elevation clusters of the Alps and Carpathian Arc. Notably, we find little potential for future growth increases (−10 to +2%) at the poleward leading edge in southern Scandinavia. Because in this region beech growth is found to be primarily water‐limited, a northward shift in its distributional range will be constrained by water availability.

Development and characterization of a novel variant of long-acting bovine follicle-stimulating hormone (brscFSH) - Oscar Ignacio Cabeza; Natalie Parra; Rita Cerro; Rodrigo Mansilla; Roxana Zuniga Sanchez; Miguel Gutierrez-Reinoso; Eduardo H. Escribano; Raul Castillo; Lleretny Rodriguez-Alvarez; Kaio Tavares; Saul Gaudencio; Leonardo Martins; et al. (Theriogenology, 2024)

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

The connection of the Costa Rica Coastal Current with the West Mexican Current in the Gulf of Tehuantepec - Martin Alfredo Terrazas Silva; David Alberto Salas de León; Maria Luisa Machain Castillo; María Adela Monreal Gómez (Continental Shelf Research, 2024)

Exploring proteasome inhibition using atomic weighted vector indices and machine learning approaches - Yoan Martínez-López; Juan A. Castillo-Garit; Gerardo M. Casanola-Martin; Bakhtiyor Rasulev; Ansel Y. Rodríguez-Gonzalez; Oscar Martínez-Santiago; Stephen J. Barigye (Molecular Diversity, 2024)

Characterizing phenotypic data of Peromyscus leucopus compared to C57BL/6J Mus musculus and diversity outbred (DO) Mus musculus - Lauren A. Wimer; Asia Davis-Castillo; Sofiya Galkina; Serban Ciotlos; Cavan Patterson; Leandro Prado; Maria Castro Munoz; Nicolas Martin; Sharon Epstein; Nicholas Schaum; Simon Melov (GeroScience, 2024)
Translational research is commonly performed in the C57B6/J mouse strain, chosen for its genetic homogeneity and phenotypic uniformity. Here, we evaluate the suitability of the white-footed deer mouse ( Peromyscus leucopus ) as a model organism for aging research, offering a comparative analysis against C57B6/J and diversity outbred (DO) Mus musculus strains. Our study includes comparisons of body composition, skeletal muscle function, and cardiovascular parameters, shedding light on potential applications and limitations of P. leucopus in aging studies. Notably, P. leucopus exhibits distinct body composition characteristics, emphasizing reduced muscle force exertion and a unique metabolism, particularly in fat mass. Cardiovascular assessments showed changes in arterial stiffness, challenging conventional assumptions and highlighting the need for a nuanced interpretation of aging-related phenotypes. Our study also highlights inherent challenges associated with maintaining and phenotyping P. leucopus cohorts. Behavioral considerations, including anxiety-induced responses during handling and phenotyping assessment, pose obstacles in acquiring meaningful data. Moreover, the unique anatomy of P. leucopus necessitates careful adaptation of protocols designed for Mus musculus . While showcasing potential benefits, further extensive analyses across broader age ranges and larger cohorts are necessary to establish the reliability of P. leucopus as a robust and translatable model for aging studies.

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Spatio-temporal trends of mercury levels in alluvial gold mining spoils areas monitored between rainy and dry seasons in the Peruvian Amazon - Edwin Becerra-Lira; Liset Rodriguez-Achata; Adenka Muñoz Ushñahua; Ronald Corvera Gomringer; Evert Thomas; Jorge Garate-Quispe; Litcely Hilares Vargas; Pedro Romel Nascimento Herbay; Luis Alfredo Gamarra Miranda; Eleuterio Umpiérrez; Juan Antonio Guerrero Barrantes; Martin Pillaca; et al. (Environmental Research, 2024)

Incorporating high-resolution climate, remote sensing and topographic data to map annual forest growth in central and eastern Europe - Jernej Jevšenak; Marcin Klisz; Jiří Mašek; Vojtěch Čada; Pavel Janda; Miroslav Svoboda; Ondřej Vostarek; Vaclav Treml; Ernst van der Maaten; Andrei Popa; Ionel Popa; Marieke van der Maaten-Theunissen; et al. (Science of The Total Environment, 2024)

Assessing the effects of oxytocin in changes of core body temperature during LPS-induced endotoxemia: A novel approach using Extended Poincaré Plot Analysis - Óscar Javier López-Troncoso; José Javier Reyes-Lagos; Martin Hadamitzky; Miguel Ángel Peña-Castillo; Juan Carlos Echeverría; Laura Lückemann; Manfred Schedlowski; Gustavo Pacheco-López (Journal of Thermal Biology, 2024)

Meshing strategies for 3d geo-electromagnetic modeling in the presence of metallic infrastructure - Octavio Castillo-Reyes; Paula Rulff; Evan Schankee Um; Adrian Amor-Martin (Computational Geosciences, 2023)
In 3D geo-electromagnetic modeling, an adequate discretisation of the modeling domain is crucial to obtain accurate forward responses and reliable inversion results while reducing the computational cost. This paper investigates the mesh design for subsurface models, including steel-cased wells, which is relevant for many exploration settings but still remains a numerically challenging task. Applying a goal-oriented mesh refinement technique and subsequent calculations with the high-order edge finite element method, simulations of 3D controlled-source electromagnetic models in the presence of metallic infrastructure are performed. Two test models are considered, each needing a distinct version of approximation methods to incorporate the conductive steel casings of the included wells. The influence of mesh quality, goal-oriented meshing, and high-order approximations on problem sizes, computational cost, and accuracy of electromagnetic responses is investigated. The main insights of our work are: (a) the applied numerical schemes can mitigate the computational burden of geo-electromagnetic modeling in the presence of steel artifacts; (b) investigating the processes driving the meshing of models with embedded metallic infrastructures can lead to adequate strategies to deal with the inversion of such electromagnetic data sets. Based on the modeling results and analyses conducted, general recommendations for modeling strategies are proposed when performing simulations for challenging steel infrastructure scenarios.

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Holistic fuzzy logic methodology to assess positive energy district (PathPED) - Tony Castillo-Calzadilla; Roberto Garay-Martinez; Cristina Martin Andonegui (Sustainable Cities and Society, 2023)

Water-rich C-type asteroids as early solar system carbonate factories - Victoria Froh; Maitrayee Bose; Martin D. Suttle; Jacopo Nava; Luigi Folco; Lynda B. Williams; Julie Castillo-Rogez (Icarus, 2023)

Palaeozoic – Early Mesozoic geological history of the Antarctic Peninsula and correlations with Patagonia: Kinematic reconstructions of the proto-Pacific margin of Gondwana - Teal R. Riley; Alex Burton-Johnson; Michael J. Flowerdew; Fernando Poblete; Paula Castillo; Francisco Hervé; Philip T. Leat; Ian L. Millar; Joaquin Bastias; Martin J. Whitehouse (Earth-Science Reviews, 2023)

Integrated evidence‐based extent of occurrence for North American bison ( Bison bison ) since 1500 CE and before - Jeff M. Martin; Rachel A. Short; Glenn E. Plumb; Lauren Markewicz; Dirk H. Van Vuren; Bradly Wehus‐Tow; Erik Otárola‐Castillo; Matthew E. Hill (Ecology, 2023)
Following the near extinction of bison ( Bison bison ) from its historic range across North America in the late 19th century, novel bison conservation efforts in the early 20th century catalyzed a popular widespread conservation movement to protect and restore bison among other species and places. Since Allen's initial delineation (1876) of the historic distribution of North American bison, subsequent attempts have been hampered by knowledge gaps about bison distribution and abundance prior to and following colonial arrival and settlement. For the first time, we applied a multidisciplinary approach to assemble a comprehensive, integrated geographic database and meta‐analysis of bison occurrence over the last 200,000 years, with particular emphasis on the 450 years before present. We combined paleontology, archaeology, and historical ecology data for our database, which totaled 6438 observations. We derived the observations from existing online databases, published literature, and first‐hand exploration journal entries. To illustrate the conservative maximum historical extent of occurrence of bison, we created a concave hull using observations occurring over the last 450 years ( n = 3379 observations), which is the broadly accepted historical benchmark at 1500 CE covering 59% of the North American continent. Although this distribution represents a historic extent of occurrence—merely delineating the maximum margins of the near‐continental distribution—it does not replace a density‐based approach reconstructing potential historical range distributions, which identifies core and marginal ranges. However, we envision the observations contained in this database will contribute to further research in the increasingly evidence‐based disciplines of bison ecology, evolution, rewilding, management, and conservation. There are no copyright or proprietary restrictions on these data, and this data paper should be cited when the data are reused.

Astroglial and oligodendroglial markers in the cuprizone animal model for de- and remyelination - Maria de los Angeles Castillo-Rodriguez; Stefan Gingele; Lara-Jasmin Schröder; Thiemo Möllenkamp; Martin Stangel; Thomas Skripuletz; Viktoria Gudi (Histochemistry and Cell Biology, 2022)
Myelin loss with consecutive axon degeneration and impaired remyelination are the underlying causes of progressive disease in patients with multiple sclerosis. Astrocytes are suggested to play a major role in these processes. The unmasking of distinct astrocyte identities in health and disease would help to understand the pathophysiological mechanisms in which astrocytes are involved. However, the number of specific astrocyte markers is limited. Therefore, we performed immunohistochemical studies and analyzed various markers including GFAP, vimentin, S100B, ALDH1L1, and LCN2 during de- and remyelination using the toxic murine cuprizone animal model. Applying this animal model, we were able to confirm overlapping expression of vimentin and GFAP and highlighted the potential of ALDH1L1 as a pan-astrocytic marker, in agreement with previous data. Only a small population of GFAP-positive astrocytes in the corpus callosum highly up-regulated LCN2 at the peak of demyelination and S100B expression was found in a subset of oligodendroglia as well, thus S100B turned out to have a limited use as a particular astroglial marker. Additionally, numerous GFAP-positive astrocytes in the lateral corpus callosum did not express S100B, further strengthening findings of heterogeneity in the astrocytic population. In conclusion, our results acknowledged that GFAP, vimentin, LCN2, and ALDH1L1 serve as reliable marker to identify activated astrocytes during cuprizone-induced de- and remyelination. Moreover, there were clear regional and temporal differences in protein and mRNA expression levels and patterns of the studied markers, generally between gray and white matter structures.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Establishment of five new genera in the family Geminiviridae: Citlodavirus, Maldovirus, Mulcrilevirus, Opunvirus, and Topilevirus - Philippe Roumagnac; Jean-Michel Lett; Elvira Fiallo-Olivé; Jesús Navas-Castillo; F. Murilo Zerbini; Darren P. Martin; Arvind Varsani (Archives of Virology, 2022)

Taxonomy update for the family Alphasatellitidae: new subfamily, genera, and species - Arvind Varsani; Darren P. Martin; John W. Randles; H. Josef Vetten; John E. Thomas; Elvira Fiallo-Olivé; Jesús Navas-Castillo; Jean-Michel Lett; F. Murilo Zerbini; Philippe Roumagnac; Bruno Gronenborn (Archives of Virology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Imaging the Chicxulub Central Crater Zone from Large-Scale Seismic Acoustic Wave Propagation and Gravity Modeling - Carlos Ortiz-Aleman; Ronald Martin; Jaime Urrutia-Fucugauchi; Mauricio Orozco del Castillo; Mauricio Nava-Flores (Pure and Applied Geophysics, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Depositional environments and landscapes of the upper Miocene Ipururo Formation at Shumanza, Subandean Zone, northern Peru - Augustin Feussom Tcheumeleu; Séverine Fauquette; Angélica Aliaga Castillo; Camila Martinez; Federico Moreno; Rosa E. Navarrete; Francisco Parra; Frank P. Wesselingh; Rodolfo Salas-Gismondi; Rafael Varas-Malca; Martin Roddaz; Pierre-Olivier Antoine (Palaeobiodiversity and Palaeoenvironments, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A multidrug-resistant microorganism infection risk prediction model: development and validation in an emergency medicine population - Juan González del Castillo; Agustín Julián-Jiménez; Julio Javier Gamazo-Del Rio; Eric Jorge García-Lamberechts; Ferrán Llopis-Roca; Josep María Guardiola Tey; Mikel Martínez-Ortiz de Zarate; Carmen Navarro Bustos; Pascual Piñera Salmerón; Jesús Álvarez-Manzanares; María del Mar Ortega Romero; Martin Ruiz Grinspan; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Spatial patterns of climate–growth relationships across species distribution as a forest management tool in Moncayo Natural Park (Spain) - Edurne Martínez del Castillo; Luis Alberto Longares; Roberto Serrano-Notivoli; Ute G. W. Sass-Klaassen; Martin de Luis (European Journal of Forest Research, 2019)

Chilling and forcing temperatures interact to predict the onset of wood formation in Northern Hemisphere conifers - Nicolas Delpierre; Ségolène Lireux; Florian Hartig; Jesus Julio Camarero; Alissar Cheaib; Katarina Čufar; Henri Cuny; Annie Deslauriers; Patrick Fonti; Jožica Gričar; Jian‐Guo Huang; Cornelia Krause; et al. (Global Change Biology, 2019)
The phenology of wood formation is a critical process to consider for predicting how trees from the temperate and boreal zones may react to climate change. Compared to leaf phenology, however, the determinism of wood phenology is still poorly known. Here, we compared for the first time three alternative ecophysiological model classes ( threshold models, heat‐sum models and chilling‐influenced heat‐sum models) and an empirical model in their ability to predict the starting date of xylem cell enlargement in spring, for four major Northern Hemisphere conifers ( Larix decidua, Pinus sylvestris , Picea abies and Picea mariana ). We fitted models with Bayesian inference to wood phenological data collected for 220 site‐years over Europe and Canada. The chilling‐influenced heat‐sum model received most support for all the four studied species, predicting validation data with a 7.7‐day error, which is within one day of the observed data resolution. We conclude that both chilling and forcing temperatures determine the onset of wood formation in Northern Hemisphere conifers. Importantly, the chilling‐influenced heat‐sum model showed virtually no spatial bias whichever the species, despite the large environmental gradients considered. This suggests that the spring onset of wood formation is far less affected by local adaptation than by environmentally driven plasticity. In a context of climate change, we therefore expect rising winter–spring temperature to exert ambivalent effects on the spring onset of wood formation, tending to hasten it through the accumulation of forcing temperature, but imposing a higher forcing temperature requirement through the lower accumulation of chilling.

Alphasatellitidae: a new family with two subfamilies for the classification of geminivirus- and nanovirus-associated alphasatellites - Rob W. Briddon; Darren P. Martin; Philippe Roumagnac; Jesús Navas-Castillo; Elvira Fiallo-Olivé; Enrique Moriones; Jean-Michel Lett; F. Murilo Zerbini; Arvind Varsani (Archives of Virology, 2018)

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Atom based linear index descriptors in QSAR-machine learning classifiers for the prediction of ubiquitin-proteasome pathway activity - Gerardo M. Casañola-Martin; Hai Pham-The; Juan A. Castillo-Garit; Huong Le-Thi-Thu (Medicinal Chemistry Research, 2018)

Decoupling between the hand territory and the default mode network after bilateral arm transplantation: four-year follow-up case study - Carlos R. Hernandez-Castillo; Jörn Diedrichsen; Erika Aguilar-Castañeda; Martin Iglesias (Brain Imaging and Behavior, 2018)

Capulavirus and Grablovirus: two new genera in the family Geminiviridae - Arvind Varsani; Philippe Roumagnac; Marc Fuchs; Jesús Navas-Castillo; Enrique Moriones; Ali Idris; Rob W. Briddon; Rafael Rivera-Bustamante; F. Murilo Zerbini; Darren P Martin (Archives of Virology, 2017)

Sampling method evaluation and empirical model fitting for count data to estimate densities of Oligonychus perseae (Acari: Tetranychidae) on ‘Hass’ avocado leaves in southern California - Jesús R. Lara; Naseem T. Saremi; Martin J. Castillo; Mark S. Hoddle (Experimental and Applied Acarology, 2016)

Revision of Begomovirus taxonomy based on pairwise sequence comparisons - Judith K. Brown; F. Murilo Zerbini; Jesús Navas-Castillo; Enrique Moriones; Roberto Ramos-Sobrinho; José C. F. Silva; Elvira Fiallo-Olivé; Rob W. Briddon; Cecilia Hernández-Zepeda; Ali Idris; V. G. Malathi; Darren P. Martin; et al. (Archives of Virology, 2015)

Common climatic signals affecting oak tree-ring growth in SE Central Europe - Katarina Cufar; Michael Grabner; András Morgós; Edurne Martínez del Castillo; Maks Merela; Martin de Luis (Trees, 2014)

Establishment of three new genera in the family Geminiviridae: Becurtovirus, Eragrovirus and Turncurtovirus - Arvind Varsani; Jesús Navas-Castillo; Enrique Moriones; Cecilia Hernández-Zepeda; Ali Idris; Judith K. Brown; F. Murilo Zerbini; Darren P. Martin (Archives of Virology, 2014)

Revisiting the classification of curtoviruses based on genome-wide pairwise identity - Arvind Varsani; Darren P. Martin; Jesús Navas-Castillo; Enrique Moriones; Cecilia Hernández-Zepeda; Ali Idris; F. Murilo Zerbini; Judith K. Brown (Archives of Virology, 2014)

Axonal regeneration after spinal cord injury in zebrafish and mammals: differences, similarities, translation - Katarina Vajn; Jeffery A. Plunkett; Alexis Tapanes-Castillo; Martin Oudega (Neuroscience Bulletin, 2013)

A genome-wide pairwise-identity-based proposal for the classification of viruses in the genus Mastrevirus (family Geminiviridae) - Brejnev Muhire; Darren P. Martin; Judith K. Brown; Jesús Navas-Castillo; Enrique Moriones; F. Murilo Zerbini; Rafael Rivera-Bustamante; V. G. Malathi; Rob W. Briddon; Arvind Varsani (Archives of Virology, 2013)

Phenotypic–genotypic resistance in Salmonella spp. isolated from cattle carcasses from the north central zone of the State of Mexico - Jorge Antonio Varela-Guerrero; Martin Talavera-Rojas; Adriana del Carmen Gutiérrez-Castillo; Nydia Edith Reyes-Rodríguez; Jesús Vázquez-Guadarrama (Tropical Animal Health and Production, 2013)

Effect of rice polishing and phytase supplementation in diets on productive behavior of broilers - Jaime Salinas-Chavira; Zaira N. Montoya-Chávez; Jose Castañeda-Licón; Lorenzo A. Duran-Meléndez; David López-Cantú; Fidel Infante-Rodríguez; Jose O. Jasso-Obregón; Martin F. Montano-Gomez; Ramón F. García-Castillo (Tropical Animal Health and Production, 2013)

Simultaneous detection of the IPN and ISA viruses in outbreaks of clinical disease and mortality in farmed Atlantic salmon, Salmo salar L., in Chile - M Cortez‐San Martin; A Rivas‐Aravena; S Guajardo; M T Castillo; M Jashes; A M Sandino; E Spencer (Journal of Fish Diseases, 2012)

Cadmium, copper, lead, and zinc in Mugil cephalus from seven coastal lagoons of NW Mexico - Martin G. Frías-Espericueta; J. Isidro Osuna-López; Martha A. Jiménez-Vega; Daniel Castillo-Bueso; Maria D. Muy-Rangel; Werner Rubio-Carrasco; Gabriel López-López; Gildardo Izaguirre-Fierro; Domenico Voltolina (Environmental Monitoring and Assessment, 2011)

Effect of dietary protein source and time on alkaline proteolytic activity of Nile tilapia (Oreochromis niloticus) - Mayra L. González-Félix; Francisco J. Castillo-Yañez; Víctor M. Ocaño-Higuera; Martin Perez-Velazquez; Venecia Cota-Moreno; José Lozano-Taylor (Fish Physiology and Biochemistry, 2010)

Estimation of tropical forest structure from SPOT-5 satellite images - Miguel Angel Castillo-Santiago; Martin Ricker; Bernardus H. J. de Jong (International Journal of Remote Sensing, 2010)

Characterization and comparison of the properties of sarcoma cell lines in vitro and in vivo - Joslyn MILLS; Tulio MATOS; Elizabeth CHARYTONOWICZ; Todd HRICIK; Mireia CASTILLO-MARTIN; Fabrizio REMOTTI; Francis Y LEE; Igor MATUSHANSKY (Human Cell, 2009)

Physical and chemical limnology of a wind-swept tropical highland reservoir - Martin Merino-Ibarra; Emiliano Monroy-Ríos; Gloria Vilaclara; Fermin S. Castillo; Margarita E. Gallegos; Jorge Ramírez-Zierold (Aquatic Ecology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)